Accessing the triplet state of perylenediimide by radical-enhanced intersystem crossing. Issue 22 (24th May 2022) - Mayländer, Maximilian; Nolden, Oliver; Franz, Michael; Chen, Su; Bancroft, Laura; Qiu, Yunfan; Wasielewski, Michael R.; Gilch, Peter; Richert, Sabine
Abstract : The triplet state of PDI can be sensitized efficiently by radical-enhanced intersystem crossing. A detailed study of several related structures allows us to propose new strategies to optimize triplet formation in materials for optoelectronic devices. Abstract : Owing to their exceptional photophysical properties and high photostability, perylene diimide (PDI) chromophores have found various applications as building blocks of materials for organic electronics. In many light-induced processes in PDI derivatives, chromophore excited states with high spin multiplicities, such as triplet or quintet states, have been revealed as key intermediates. The exploration of their properties and formation conditions is thus expected to provide invaluable insight into their underlying photophysics and promises to reveal strategies for increasing the performance of optoelectronic devices. However, accessing these high-multiplicity excited states of PDI to increase our mechanistic understanding remains a difficult task, due to the fact that the lowest excited singlet state of PDI decays with near-unity quantum yield to its ground state. Here we make use of radical-enhanced intersystem crossing (EISC) to generate the PDI triplet state in high yield. One or two 2, 2, 6, 6-tetramethylpiperidinyloxyl (TEMPO) stable radicals were covalently attached to the imide position of PDI chromophores with and without p-tert -butylphenoxy core substituents. By combining femtosecond UV-vis transient absorption and transient electron paramagnetic resonance spectroscopies, we demonstrate strong magnetic exchange coupling between the PDI triplet state and TEMPO, resulting in the formation of excited quartet or quintet states. Important differences in the S1 state deactivation rate constants and triplet yields are observed for compounds bearing PDI moieties with different core substitution patterns. We show that these differences can be rationalized by considering the varying importance of competitive excited state decay processes, such as electron and excitation energy transfer. The comparison of the results obtained for different PDI–TEMPO derivatives leads us to propose design guidelines for optimizing the efficiency of triplet sensitization in molecular assemblies by EISC.